RANCANG BANGUN APLIKASI SIMPAN PINJAM PADA KOPERASI SAMI BERBASIS WEB - Maimunah Maimunah; Devi Isnaeni; Ade Ferdiansyah (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Cooperative Ardhia Satya Mandiri ( KOSAMI ) requires good data processing system and integrated in order to facilitate the decision-making and create a good standard of service . Moreover, if the data associated with the financial and customer . Data and information is easily accessible by the Cooperative Ardhia Satya Mandiri ( KOSAMI ) , employees , and customers are needed to support the performance of the cooperative in question . This study discusses the application of savings and credit program consisting of members of the input form , the form of borrowing , payment form , the form member , and payment reports . The programming language used to program these applications is the PHP programming language and the SQL Server database . This research was made through through the stages of ( 1 ) identification , ie identifying the problem , ( 2 ) Understand , understand the working of the existing system , ( 3 ) analysis , which analyzes the system , ( 4 ) Report , which report the results of the analysis.